PENGELOLAAN SARANA PRASARANA RINTISAN SEKOLAH KATAGORI MANDIRI(STUDI SITUS SMA NEGERI 1 TOROH KABUPATEN GROBOGAN TAHUN 2010/2011) - SUDARSIH, SUDARSIH (2011)
Educationfacilityisoneofimportantandmainresourcesinsupportinglearning processinaschool,thusitneedsimprovementinutilizationandmanagementinorder thattheobjectiveispursued.Tooptimizethesupply,maintenance,utilizationandcontrol ofthosefacilityneedsineachtypeandgradeofeducation,itneedsadaptationoffacility management.Schoolisrequiredtohaveindependencetoregulateandmindschool interestasthenecessityandabilityandbebasedonaspirationandparticipationofthe stakeholder. Torealizeandregulateit,thegovernmentthroughgovernmentprovisionofPP No19of2005aboutNationalEducationStandard,regardingeducationfacilitystandard nationallyonchapterVIIinarticle42.Theobjectiveofthestudyistodescribe characteristicsoffacilitymanagement,todescribefacilityprovidingmanagement,andto describemaintenancemanagementinIndependentCategorySchoolProspectofSMA Negeri1TorohKabupateninGroboganRegency. Itisdescriptivequalitativeresearchinvolvingillustrationofresearchobject.The datacollectionmethodsusedareinterview,observation,anddocumentandparticipative observation.Thedatasourceusedinthisresearchis(1)Informant(Principal,Vice principaloffacility,teacher,administrator,andschoolcommittee),(2)Documentand recordrelatingtofacilitymanagement,(3)placeandeventbycollectingdataand informationconcerninggeographicalandactivityaboutfacilitymanagement,informof wordsandactionobservedandinterviewed.DataareanalyzedbyreferringtoMilesand Hubermannamelydatareduction,datadisplay,andconclusion/verification.Thevalidity ofdataisachievedbyusingtriangulationbyperformingcheckingdatatowardtwoor moreinformationsources,suchasrecheckingbyusingsamequestionindifferenttime andcrosscheckingbyinterviewingwithotherparticipant.Resultofthestudyisthe managementprocessoffacilityincludingfacilityprovidingmanagementfrom governmentgrant,charity,andschoolfund,utilizingoffacilityisbasedonscheduleand unscheduled,byallschoolstakeholderbasedontheirnecessity,maintenanceofschoolfacilityisperformedcontinuously,periodically,emergency,preventive,inorderthatthe facilityisreadytouse,safe,maintained,safeforuser,comfortsothatitcansmooth teachinglearningprocess.Themaintenanceinvolvestheentireschoolstakeholder.